Tumor necrosis factor α mediates apoptosis of brown adipocytes and defective brown adipocyte function in obesity - Nisoli, Enzo (The National Academy of Sciences, 2000)
Severe quantitative and qualitative brown adipocyte defects are common in obesity. To investigate whether aberrant expression of tumor necrosis factor α (TNF-α) in obesity is involved in functional brown fat atrophy, we have studied genetically obese (ob/ob) mice with targeted null mutations in the genes encoding the two TNF receptors. The absence of both TNF receptors or p55 receptor alone resulted in a significant reduction in brown adipocyte apoptosis and an increase in β(3)-adrenoreceptor and uncoupling protein-1 expression in obese mice. Increased numbers of multilocular functionally active brown adipocytes, and improved thermoregulation was also observed in obese animals lacking TNF-α function. These results indicate that TNF-α plays an important role in multiple aspects of brown adipose tissue biology and mediates the abnormalities that occur at this site in obesity.